2016
DOI: 10.1097/md.0000000000005175
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 gene polymorphisms are associated with type A aortic dissection and aortic diameters in patients

Abstract: Matrix metalloproteinases-2 (MMP-2) plays an important role in the pathogenesis of type A aortic dissection (AD). The aim of this study was to evaluate the association of 3 single nucleotide polymorphisms (SNPs) in the MMP-2 gene with type A AD risk and aortic diameters in patients. We performed a case–control study with 172 unrelated type A AD patients and 439 controls. Three SNPs rs11644561, rs11643630, and rs243865 were genotyped through the MassARRAY platform. Allelic associations of SNPs and SNP haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…MMP2rs11643630T/G is located in approximately 4 and 2.6 kb upstream of transcription initiation site and may be involved in the disease in a complex way. 26 Our results showed a strong correlation between the rs11643630 G allele and a deceased risk for TAD. In an individual study, Ruvolo et al found that…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…MMP2rs11643630T/G is located in approximately 4 and 2.6 kb upstream of transcription initiation site and may be involved in the disease in a complex way. 26 Our results showed a strong correlation between the rs11643630 G allele and a deceased risk for TAD. In an individual study, Ruvolo et al found that…”
Section: Discussionsupporting
confidence: 55%
“…In our meta‐analysis, no obvious association of MMP2rs1053605 polymorphism with overall AA was detected. MMP2rs11643630T/G is located in approximately 4 and 2.6 kb upstream of transcription initiation site and may be involved in the disease in a complex way . Our results showed a strong correlation between the rs11643630 G allele and a deceased risk for TAD.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracoabdominal was the most frequently involved district. 30,31 In our patients, the presence of intimal thickening and plaques with or without stenoses likely reflects the coexistence of IADE and systemic atherosclerosis. However, the reported findings are not of univocal interpretation from a pathogenic point of view and need to be confirmed in larger patient series.…”
Section: Discussionmentioning
confidence: 66%
“…26 Likewise, a proteolytic imbalance induced by specific metalloproteinase polymorphisms has also been related to the development of thoracic aorta dissection and coronary artery ectasia. 30,31 In our patients, the presence of intimal thickening and plaques with or without stenoses likely reflects the coexistence of IADE and systemic atherosclerosis. In the past, due to the fact that IADE and atherosclerosis share similar risk factors, these disorders were pos- In the GENIC Study, the lack of any association between IADE and several ultrasonographic markers of atherosclerosis such as common carotid arteries intima-media thickness and carotid plaques corroborated on clinical grounds the hypothesis that IADE is not an ectatic variant of atherothrombotic disease.…”
Section: Discussionmentioning
confidence: 66%
“…[61,62] Several studies have shown that SNPs could explain differences in genetic susceptibility to different diseases. [63,64] In recent years, extensive pharmacogenomics investigations have been performed to optimize MTX therapy for RA patients through genotyping and/or gene-expression-based tests. These tests were primarily based on mRNA and included transporters, enzymes, and metabolites genes [57] ; however, the majority of the findings were inconclusive and inconsistent, even for classical candidate gene polymorphisms.…”
Section: Discussionmentioning
confidence: 99%